Embracing the Future: Creative Industries for Environment and Advanced Society 5.0 in a Post-Pandemic Era : Proceedings of the 8th Bandung Creative Movement International Conference on Creative Industries (8th BCM 2021), Bandung, Indonesia, 9 September 2021 - Rahmiati Aulia; Diani Apsari; Sri Maharani Budi Haswati; Hana Faza Surya Rusyda; Aisyi Syafikarani; Angelia Lionardi; Setiamurti Rahardjo; Ariesa Farida; Wibisono Tegar Guna Putra; Yelly Andriani Barlian (Routledge, 2023)
By delivering the mindful writings from our selected authors, this book portrays one big idea: a new Human-Centered society that balances economics to resolve problems, especially in the use of an integrated area in cyberspace, physical space, and how it impacts the creative industries. Through The 8th Bandung Creative Movement, scholars from 15 Universities around the Asian and European countries have discussed this issue where Human-Centered society became the main consideration in the development.Three topics are presented to the readers. Firstly,'Sustainable Cities and Communities'explores the sub-fields that construct a more sustainable environment for society post-pandemic era, such as technologies, transportation, interior design, architecture, urban planning, etc. While'Art and Design: Recontextualization of Nusantara Tradition and Indigenous Culture'concerned the novel perspectives on recognizing cultural aspects that shape the face of creative industry, from cultural identity, visual and performing arts, pop culture to language and media. The last topic,'Changes and Dynamics in The Creative Industries,'reviews the creative approach toward the industry's current trends, including marketplace, destination branding, or digital culture ecosystem.This book will enrich the mind of everybody who is an enthusiast of innovative research on creative industries, human-centered technologies, environmental design, and excellent society 5.0 post-pandemic era.